IMPROVING THE QUALITY OF SOCIAL STUDIES LEARNING: THE IMPLEMENTATION OF PROBLEM-BASED LEARNING FOR THE INTELLECTUAL AND EMOTIONAL INTELLIGENCE OF ELEMENTARY SCHOOL STUDENTS - Aisyah Elvina Sari; Aramudin (Universitas Islam Negeri Mataram, 2025)
This study is motivated by the issue of low learning motivation and the limited development of intellectual and emotional intelligence in Social Studies (IPS) learning at SDN 034 Tarai Bangun. The teaching of IPS, which is still dominated by passive lecture methods, causes students to be less cognitively and affectively engaged, thus hindering the development of critical thinking skills, collaboration abilities, and emotional regulation. This issue led the researcher to explore the implementation of the Problem-Based Learning (PBL) model as an innovative solution that can simultaneously integrate the development of learning motivation, intellectual intelligence (IQ), and emotional intelligence (EQ). The aim of this study is to analyze the implementation of the PBL model in IPS learning and to explain its impact on improving learning motivation, intellectual intelligence, and emotional intelligence of fourth-grade students at SDN 034 Tarai Bangun. The research method used is a qualitative approach with a case study design. Data collection techniques include participatory observation of the learning process, in-depth interviews with teachers and students, and documentation in the form of analysis of the Lesson Plan (RPP) and student work results. The results of the study indicate that